Proceedings of the symposium on transient ground water hydraulics - Maasland, D. E. L. (Dirk Elbert Leo), 1934-, author; Bittinger, Morton W., author; Civil Engineering Section, Colorado State University, publisher (Colorado State University. Libraries, 1963)
The symposium was held at Colorado State University in Fort Collins, Colorado on July 25-27, 1963.
CER63DEM-MWB70.
December 1963.
Issued with supplements.
Errata included.
Keywords: Groundwater; Hydraulics